MR imaging of the brain: tumors - Sartor, Klaus (European radiology, 1999)
The radiologic modality that most likely provides the imaging information needed in a patient suspected of having a brain tumor is MR imaging. A brain tumor can be reliably ruled out if the MR examination is performed properly and experts interpret the results as negative. If there is a tumor, however, its exact location and topography must be determined. Important for therapy and prognosis are also tumor properties such as histologic type and grade, as well as effects on adjacent brain structures. Although potentially a noninvasive method of in vivo neuropathology, MR is still far from being sufficiently specific, as dissimilar lesions may look the same despite the use of refined imaging protocols. The evolution of MR imaging continues, however, making further methodologic improvement likely. Presently, advanced methods, such as diffusion- and perfusion-weighted MR imaging, functional MR imaging, neuronavigation based on MR imaging data, and the use of MR imaging during surgery (intraoperative MR imaging), influence the way patients are treated. Likewise, follow-up imaging (monitoring) of tumor patients by MR has become more effective, and experience has shown how to distinguish reactive changes from recurrent tumor. In the future, MR imaging may gain importance in the development of novel therapeutic concepts.
Gesehen am 11.03.2021